Investigation of the influence of A-pillar on passive safety of a vehicle in case of rollover - Dzerkelis, Vytautas; Bazaras, Žilvinas; Lukoševičius, Vaidas (Transport, 2015)
The need for the means ensuring passive safety of a vehicle is becoming increasingly emphasized in the area of transport engineering. This area becomes particularly relevant when restoration of the damaged load bearing structures in vehicles is concerned. When performing restoration and modification of the vehicles according to specific needs or repairing them after traffic accidents, the lack of norms giving formalized determination of passive safety and recommendations for its assurance becomes obvious. Computational model of the roof structure developed in LSDYNA is presented, the weld intended for the structure joints is modelled, and residual stresses due to welding process are taken into account, the most effective model of weld location for A-pillar is selected and the influence of A-pillar on the strength of vehicle’s roof structure is determined in case of quasi-static compression.